Study of a magnetorheological fluid submitted to a uniform magnetic field (2017)
ABSTRACT: In this work, the rheological and hyperfine properties of a magnetorheological fluid (MRF) under the action of a uniform external magnetic field are analysed. Powders of native mineral magnetite of micrometric particle size, after a pulverization process, form the solute of these fluids. The sizes of these samples are selected by sieving in order to obtain sizes of around 20μm and 45μm. The powders are characterized by means of Mössbauer spectroscopy to analyse their stoichiometry giving rise to a non-stoichiometric magnetite Fe2.96O4 in addition to a hematite component. Result of viscosity and shear stress in the low-speed regime were analysed using the Hershel Buckley method. In particular, the case of surface tension it decreases with the application of a uniform magnetic flux density, which is understood in terms of a phase separation due to the formation of mesoscopic structures, thus decreasing the cohesion force and increasing the adhesion force.